(untitled) (International scientific-electronic journal “Pioneering studies and theories”, 2026)
This article is devoted to the international experience in marketing management and improving production efficiency through the application of lean management concepts and the REFA method. It demonstrates how the integration of marketing strategies with tools for enhancing production efficiency contributes to cost reduction, improvement of product quality, and strengthening of a company’s competitive position in international markets.